Elevated Leukocyte Azurophilic Enzymes in Human Diabetic Ketoacidosis Plasma Degrade Cerebrovascular Endothelial Junctional Proteins*. Issue 9 (September 2016) - Woo, Martin M. H.; Patterson, Eric K.; Clarson, Cheril; Cepinskas, Gediminas; Bani-Yaghoub, Mahmud; Stanimirovic, Danica B.; Fraser, Douglas D.
Abstract : Objective: Diabetic ketoacidosis in children is associated with vasogenic cerebral edema, possibly due to the release of destructive polymorphonuclear neutrophil azurophilic enzymes. Our objectives were to measure plasma azurophilic enzyme levels in children with diabetic ketoacidosis, to correlate plasma azurophilic enzyme levels with diabetic ketoacidosis severity, and to determine whether azurophilic enzymes disrupt the blood-brain barrier in vitro. Design: Prospective clinical and laboratory study. Setting: The Children's Hospital, London Health Sciences Centre. Subjects: Pediatric type 1 diabetes patients; acute diabetic ketoacidosis or age-/sex-matched insulin-controlled. Measurements and Main Results: Acute diabetic ketoacidosis in children was associated with elevated polymorphonuclear neutrophils. Plasma azurophilic enzymes were elevated in diabetic ketoacidosis patients, including human leukocyte elastase ( p < 0.001), proteinase-3 ( p < 0.01), and myeloperoxidase ( p < 0.001). A leukocyte origin of human leukocyte elastase and proteinase-3 in diabetic ketoacidosis was confirmed with buffy coat quantitative real-time polymerase chain reaction ( p < 0.01). Of the three azurophilic enzymes elevated, only proteinase-3 levels correlated with diabetic ketoacidosis severity ( p = 0.002). Recombinant proteinase-3 applied to human brain microvascular endothelial cells degraded both the tight junction protein occludin ( p < 0.05) and the adherens junction protein VE-cadherin ( p < 0.05). Permeability of human brain microvascular endothelial cell monolayers was increased by recombinant proteinase-3 application ( p = 0.010). Conclusions: Our results indicate that diabetic ketoacidosis is associated with systemic polymorphonuclear neutrophil activation and degranulation. Of all the polymorphonuclear neutrophil azurophilic enzymes examined, only proteinase-3 correlated with diabetic ketoacidosis severity and potently degraded the blood-brain barrier in vitro. Proteinase-3 might mediate vasogenic edema during diabetic ketoacidosis, and selective proteinase-3 antagonists may offer future vascular- and neuroprotection.